2023
DOI: 10.3847/1538-4357/acac29
|View full text |Cite
|
Sign up to set email alerts
|

GRMHD Simulations of Neutron-star Mergers with Weak Interactions: r-process Nucleosynthesis and Electromagnetic Signatures of Dynamical Ejecta

Abstract: Fast neutron-rich material ejected dynamically over ≲10 ms during the merger of a binary neutron star (BNS) can give rise to distinctive electromagnetic counterparts to the system’s gravitational-wave emission that serve as a “smoking gun” to distinguish between a BNS and an NS–black hole merger. We present novel ab initio modeling of the kilonova precursor and kilonova afterglow based on 3D general-relativistic magnetohydrodynamic simulations of BNS mergers with nuclear, tabulated, finite-temperature equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 236 publications
1
15
0
2
Order By: Relevance
“…While several numerical relativity simulations of magnetized binary neutron star mergers have been performed (e.g., Kiuchi et al 2014Kiuchi et al , 2022Dionysopoulou et al 2015;Palenzuela et al 2015Palenzuela et al , 2022Ciolfi et al 2017;Most et al 2019;Werneck et al 2023;Combi & Siegel 2023), turbulent magnetic field amplification during the collision (Price & Rosswog 2006;Kiuchi et al 2015;Aguilera-Miret et al 2020), which likely dominates the postmerger magnetic field geometry (Aguilera-Miret et al 2022), is not fully captured by current simulations (Kiuchi et al 2018). Although magnetic fields in the inspiral are not likely to strongly affect the orbital dynamics or gravitational-wave (GW) emission (Ioka & Taniguchi 2000;Zhu et al 2020), they could produce electromagnetic (EM) precursors prior to the merger (see, e.g., Hansen & Lyutikov 2001;Tsang et al 2012;Palenzuela et al 2013;Carrasco & Shibata 2020;Most & Philippov 2020, 2022aZhang 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several numerical relativity simulations of magnetized binary neutron star mergers have been performed (e.g., Kiuchi et al 2014Kiuchi et al , 2022Dionysopoulou et al 2015;Palenzuela et al 2015Palenzuela et al , 2022Ciolfi et al 2017;Most et al 2019;Werneck et al 2023;Combi & Siegel 2023), turbulent magnetic field amplification during the collision (Price & Rosswog 2006;Kiuchi et al 2015;Aguilera-Miret et al 2020), which likely dominates the postmerger magnetic field geometry (Aguilera-Miret et al 2022), is not fully captured by current simulations (Kiuchi et al 2018). Although magnetic fields in the inspiral are not likely to strongly affect the orbital dynamics or gravitational-wave (GW) emission (Ioka & Taniguchi 2000;Zhu et al 2020), they could produce electromagnetic (EM) precursors prior to the merger (see, e.g., Hansen & Lyutikov 2001;Tsang et al 2012;Palenzuela et al 2013;Carrasco & Shibata 2020;Most & Philippov 2020, 2022aZhang 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their importance, the magnetic field topology after merger remains largely unconstrained. While several numerical relativity simulations of magnetized binary neutron star mergers have been performed (e.g., Kiuchi et al 2014;Dionysopoulou et al 2015;Palenzuela et al 2015;Ciolfi et al 2017;Most et al 2019;Palenzuela et al 2022;Werneck et al 2022;Combi & Siegel 2023;Kiuchi et al 2022)…”
Section: Introductionmentioning
confidence: 99%
“…They found that the secondorder scheme overestimates the amount of proton-rich shockheated ejecta. In addition, Combi & Siegel (2023) performed convergence studies on the outflows from a BNS merger simulation and found that the highest resolution resolves the shock-heated plasma more accurately. The postmerger ejecta can be affected in a similar way.…”
Section: Outflow Measurements and Other Important Physical Componentsmentioning
confidence: 99%
“…Specifying the extraction radius can be a challenging job, and it can affect some quantities' measurements, such as velocity. In the literature, a smaller extraction radius ∼200-500 km has been used to measure the dynamical ejecta or the ejecta from magnetized postmerger HMNSs with tracers (see, e.g., Combi &Siegel 2023 andde Haas et al 2022), and each tracer has to satisfy the geodesic or Bernoulli condition to identify the unbound mass. However, the disk wind is a different scenario; the recent studies by Haddadi et al (2022) showed that if the r-process heating source terms are included in the evolution of the postmerger ejecta during a multisecond simulation, the ejecta's velocity needs to be measured at a much larger distance.…”
Section: A2 Tracer's Setup: Grid Resolution Density Threshold and Ext...mentioning
confidence: 99%
See 1 more Smart Citation